2022
DOI: 10.1007/s10643-022-01306-5
|View full text |Cite
|
Sign up to set email alerts
|

I Felt Like I was Going Crazy: Understanding Mother’s and Young Children’s Educational Experiences at Home During COVID-19

Abstract: The COVID-19 disruptions to children’s education have been a major issue for families. This study examined how demographic, family, and mental health characteristics of 375 low-income children and their mothers from the City of Toronto were associated with children’s educational experiences at home during COVID-19. Many mothers (82.3%) reported that they and their children (80.0%) experienced challenges related to children’s education at home during the pandemic. However, a small percentage of mothers (1.1%) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 54 publications
4
32
0
Order By: Relevance
“…The mental load is a form of cognitive and emotional labor taken on by women without negotiation, as a kind of boundaryless unpaid job that intrudes into other areas of their lives and affects their health and wellbeing [ 47 ]. Supporting their children’s education was a big challenge for mothers, who had to play the role of teachers and combine their children’s remote learning with their own duties [ 48 ]. Consequently, the mental health of mothers was affected by this new responsibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mental load is a form of cognitive and emotional labor taken on by women without negotiation, as a kind of boundaryless unpaid job that intrudes into other areas of their lives and affects their health and wellbeing [ 47 ]. Supporting their children’s education was a big challenge for mothers, who had to play the role of teachers and combine their children’s remote learning with their own duties [ 48 ]. Consequently, the mental health of mothers was affected by this new responsibility.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the mental health of mothers was affected by this new responsibility. It increased their levels of stress, anguish, tension, and loss of control [ 48 , 49 , 50 ]. There is evidence that the unequal distribution of labor and the exacerbation of traditional gendered roles during the lockdown impacted women’s health, especially their mental health: increased levels of stress and decreased personal satisfaction led to frustration and exhaustion [ 38 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“… 24 To address the damage that has been done to children by the Pandemic and lockdowns calls have begun for recovery plans for children, see for example Gauvin et al 25 Of course, not just children have suffered from the closure of schools but parents, and particularly mothers, had to take on the responsibility of teachers which many found had a negative impact on their mental health. 26 It would be remiss of researchers to not continue to monitor and assess the long term effects of this period on young people and their families following such an unprecedented compromise of public health.…”
Section: Nr Cluster B Lessons Directly Related To Hlb and Lifestylementioning
confidence: 99%
“…Early in the pandemic, the percentage of mothers working declined more than fathers due to domestic and child care responsibilities falling more heavily on mothers (Alon et al, 2020). Families with school-aged children were also affected by the transition to remote learning (Courtney et al, 2020;Burns et al, 2022;, with mothers being forced to adopt the role of teachers (Alon et al, 2020;Burns et al, 2022). Recent research has found that stress around parenting practices was significantly correlated with maternal overall stress levels (Babore et al, 2023).…”
Section: Impacts Of Covid-19 On Maternal Mental Healthmentioning
confidence: 99%
“…While the negative implications of COVID-19 disruptions on maternal mental health have been documented (Babore et al, 2023;Burns et al, 2022), it is widely acknowledged that further investigation is needed to fully understand the unique impacts and identify potential interventions (Wade et al, 2023). Specifically, it is crucial to investigate the potential negative effects of COVID-19 on maternal mental health for at-risk populations, such as low-income and diverse families, who may face additional stressors and barriers to accessing resources for support (Whitehead et al, 2021).…”
Section: Introductionmentioning
confidence: 99%